Spectrophotometric Determination of Butorphanol Tartrate and Telmisartan in Bulk and Pharmaceutical Formulations - Nageswara Rao, R.; Nagaraju, P.; Srinivasulu, C.; Radha Krishnamurthy, P.; Sireesha, D.; Sumanth Reddy, V. (Asian Journal of Chemistry, 2016)
Simple, sensitive and reproducible UV spectrophotometric methods have been developed for the determination of opioid analgesic and anti-hypertensive drugs, namely, butorphanol tartrate and telmisartan respectively. Both the drugs were taken in 0.1 N HCl and maximum absorbance was observed at 279 nm and 291 nm respectively. Beer’s law was obeyed in the concentration of 10–50 μg/mL for butorphanol tartrate and 2–10 μg/mL for telmisartan. There is no interference from any common pharmaceutical excipients.